(untitled) (South East Asia Journal of Public Health, 2015)
Maternal and child mortality are still higher in Bangladesh where delivery care services are associated with a number of problems. Demand-side financing, popularly well-known as maternal health care voucher, is found to reduce the financial barriers, increases choice for clients, and improves efficiency in delivery and quality of services which ultimately enhances maternal health. A cross-sectional study was conducted in different upzilas of Bhola district in Bangladesh among poor married women and found that voucher scheme receivers were 17.64 times more likely to receive delivery care services than respondents who were not part of the voucher scheme. On the other hand, the study pointed out that recipients of the voucher scheme received comparatively higher levels of delivery care services compared to those not in the voucher scheme, such as skilled birth attendance (64.2% vs. 26.3%), institutional delivery services (86.9% vs. 24.7%), and transport costs (92.5% vs. 23.1%). As the voucher scheme receivers delivery care services ensured better health status and care services than non-voucher scheme receivers in Bangladesh, the current study suggests that increasing the accessibility of voucher scheme programs will facilitate the provision of effective maternal health care services. South East Asia Journal of Public Health Vol.5(1) 2015: 39-43